Impact of platelets on major thrombosis in patients with a normal white blood cell count in essential thrombocythemia. (6th October 2020) - Buxhofer‐Ausch, Veronika; Wolf, Dominik; Sormann, Siegfried; Forjan, Ernst; Schimetta, Wolfgang; Gisslinger, Bettina; Heibl, Sonja; Krauth, Maria Theresa; Thiele, Jürgen; Ruckser, Reinhard; Gisslinger, Heinz
Abstract: Objectives: Cell counts have a significant impact on the complex mechanism of thrombosis in patients with essential thrombocythemia (ET). We recently demonstrated a considerable impact of white blood cell (WBC) counts on thrombotic risk in patients with optimized platelet counts by analysing a large anagrelide registry. In contrast, the current analysis of the registry aimed to estimate the influence of platelet counts on thrombotic risk in patients with optimized WBC counts. Methods: Cox regression analysis and Kaplan‐Meier plot were applied on all patients in the registry with optimized WBC counts. Results: By using the calculated cut‐off of 593 G/L for platelets, Cox regression analysis revealed a clear influence of elevated platelet counts on the occurrence of a major thrombotic event ( P < .001). A Kaplan‐Meier plot revealed a markedly shorter time to a major thrombotic event for patients with platelet counts above the cut‐off ( P < .001). Conclusions: The data show clear impact of platelet lowering on the thrombotic risk in ET patients with normal WBC counts. Therefore, selective platelet lowering with anagrelide appears sufficient for thrombotic risk reduction in WHO‐diagnosed ET patients lacking leukocytosis.